Injury prevention and control: reflections on the state and the direction of the field Prevención y control de lesiones por causas externas: reflexiones sobre la situación actual y futura - Maria Segui-Gomez; Mathew Miller (Instituto Nacional de Salud Pública, 2008)
OBJECTIVE: To provide an assessment of the contours of the injury field today and to raise questions about our future direction. MATERIAL AND METHODS: We classified the self-reported activities of injury centers, assessed trends in injury-related publications in peer review journals, and compared data on current funding levels. RESULTS: The 47 identified centers are more likely to focus on unintentional injuries and on prevention than on intentional injuries, biomechanics, acute care or rehabilitation. Injury-related publications have doubled over the past decade, yet remained dwarfed by those on other diseases. Funding for injury prevention remains incommensurate with the burden of injury. Within the injury field itself, publications and funding are not commensurate with the burden imposed by particular injuries. CONCLUSION: Our responsibilities as injury prevention professionals will increase not only because of the projected increase in the global burden of injury but also because of our expanded conceptualization of what the scope of injury prevention should be. The lack of clarity we project about the substantive areas of our expertise and the incommensurate funding for our efforts relative to their toll on global health represent challenges to our field's coherence and ultimate effectiveness. OBJETIVO: Valorar el estado actual del área de la prevención de lesiones y plantear el futuro de la misma. MATERIAL Y MÉTODOS: Clasificamos las actividades llevadas a cabo por diferentes centros de prevención de lesiones; recabamos información sobre la tendencia en las publicaciones en revistas científicas, y comparamos los datos sobre financiación. RESULTADOS: Evaluamos las actividades de 47 instituciones. En general, los centros realizan actividades relacionadas con las lesiones no intencionadas y en la prevención en detrimento de las lesiones intencionales, la biomecánica, asistencia sanitaria o la rehabilitación. Las publicaciones relacionadas con el área de las lesiones se han duplicado en la pasada década, aunque siguen muy por debajo de las publicaciones de otras enfermedades. La financiación destinada a la prevención de lesiones sigue siendo desproporcionada con respecto a la carga de enfermedad. Dentro del propio ámbito de la prevención de lesiones, tanto la financiación como las publicaciones no se adecuan a la carga impuesta por diferentes tipos de lesiones. CONCLUSIÓN: Nuestra responsabilidad aumenta en tanto que aumenta la carga de las lesiones sobre la población mundial y al mismo tiempo se amplía nuestra visión sobre lo que constituye una lesión. En vista de las discrepancias sobre la percepción, necesidades y escasez de financiación, hemos de estudiar con detenimiento las estrategias de futuro.